Danon's disease as a cause of hypertrophic cardiomyopathy: a systematic survey. Issue 8 (14th July 2004) - Charron, P; Villard, E; Sébillon, P; Laforêt, P; Maisonobe, T; Duboscq-Bidot, L; Romero, N; Drouin-Garraud, V; Frébourg, T; Richard, P; Eymard, B; Komajda, M
Abstract : Background: Hypertrophic cardiomyopathy (HCM) is an autosomal dominant disease caused by mutations in sarcomeric genes. However, extensive genetic screening failed to identify a mutation in about a third of cases. One possible explanation is that other diseases, caused by other genes, may mimic HCM. Objective: To investigate the possible involvement of Danon's disease, an X linked lysosomal disease, in a large population of patients with HCM. Methods: A population of 197 index cases was considered; 124 were subsequently excluded because of a mutation in sarcomeric genes and 23 because of autosomal dominant inheritance. Fifty index cases were therefore included in molecular analysis (direct sequencing) of the lysosome associated membrane protein 2 (LAMP2) gene responsible for Danon's disease. Results: Two new mutations leading to premature stop codons were identified in patients who evolved towards severe heart failure (< 25 years old): 657C>T and 173_179del. The prevalence was therefore 1% of the total population (two of 197) or 4% of enrolled index cases (two of 50). Interestingly, Danon's disease was responsible for half of the cases (two of four) with HCM and clinical skeletal myopathy but was not involved in isolated HCM (none of 41). Conclusions: Danon's disease may be involved in patients with previously diagnosed as HCM. A diagnosis strategy is proposed. To distinguish HCM from Danon's disease is important because the clinical evolution, prognosis, mode of inheritance, and therefore genetic counselling are very different.